Mycoplasma pneumoniae spread, persistence and resistance. Lessons from a single urban area. (4th October 2017) - Michael-Gayego, Ayelet; Almogy, Gal; Amit, Sharon; Stone, Lewi; Moses, Allon; Nir-Paz, Ran
Abstract: Background: Mycoplasma pneumoniae (MP) is a common respiratory pathogen. Epidemics were reported to occur every 3–4 years and usually last for 2 years. Conversely, reports from the 1970's and recently from China suggested constant high rates of MP infections. Furthermore, little information is available on disease transmission within a community during an epidemic. Here, we look at the epidemiology of MP within a 1, 000, 000-population urban community, and characterized the spatiotemporal pattern of MP transmission, and resistance. Methods: We preformed spatial-temporal analysis and simulate MP spread in the entire Jerusalem area using data obtained from the Hadassah-Hebrew University Medical Center. Since 2007 more than 8500 specimens were PCR tested and over 1000 were MP positive. We used the SpeeDx MP multiplex qPCR test to evaluate macrolide resistance, as well as sequence analysis. Results: Over a period of more than 10 years, we identified an epidemic surge that started in 2010 with a major increase in 2012. This lasted for seven years and only in 2017, a decline was noted. A mild seasonal component was observed during March, and April. During 5 years (2009 to 2014) we found 4 distinct outbreak periods in the entire area. When we divided the city area into smaller transmission zones based on geographical distance of home-addresses we could identify a source to this prolonged epidemic that appeared in Nov 2010, at the outskirts of Jerusalem, and a substantial 'epidemic peak' appeared 10 months later, affecting almost all area clusters. We reconstructed a putative spread pattern leading to this first peak and identify repeating, correlated "transmission routes", where the detection of positive events in one area are indicative of presence in epidemiologically connected areas. While in 2010 and 2011 we detected ~30% of macrolide resistance, a recent analysis of positive samples from 2016 to 2017 suggested that the current macrolides resistance rate decreased to ~11%. Conclusion: Thus, we suggest that the latest 7 yearlong MP epidemic in Jerusalem, started from a single distinct outskirt neighborhood, spreading to other areas via local transmission routes. Macrolide resistance rate reduced during the years for reasons not understood, reassuring current antibiotics for presumed severe pneumonia and MP infections. Disclosures: R. Nir-Paz, SpeeDx: Grant Investigator, Research grant